Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Dan Kompensasi Terhadap Kinerja Karyawan : Studi Karyawan Pabrik Rokok PR Konci Mas Sakti Bululawang Kabupaten Malang - Zuhdi, Afifuddin; Widarko, Agus; Slamet, Afi Rachmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of leadership style, work environment, and compensation on employee performance at PR Konci Mas Sakti, a cigarette factory in Bululawang, Malang Regency. A quantitative research approach is employed, with a population comprising factory employees. Using a non-probability sampling technique, a sample of 86 respondents was selected. Primary data was collected through questionnaires, and SPSS version 25.0 was utilized for data analysis. The results indicate that leadership style (X1), work environment (X2), and compensation (X3) have a positive and significant effect on employee performance (Y), both simultaneously and partially. Keywords: Leadership Style, Work Environment, Compensation, Employee Performance.